Real Classes Vs Online Classes: A Comparative Study on the Chosen Course of HRM Students of Gulf University, Kingdom of Bahrain - Nagi, Muskan; Bojiah, Janaki (International Journal of Emerging Technologies in Learning (iJET), 2020)
The technologically sound students of today are open and very much inclined to adopt new modes of knowledge transfer inclusive of online classes. However, there are various viewpoints related to the aspect of online classes as not much of comparative studies on real classes and online classes have been carried out in Bahrain. Therefore, the need for a research study to find out the merits and demerits of real classes and online classes was identified. The objective of the study was to find out the reasons behind the preference of a class of HRM students of Gulf University, Kingdom of Bahrain with respect to the mode of its imparting – whether it is the real classes or online classes. A class of a HRM course was taken as a sample with the same faculty handling real classes before the midterm exam and online classes after midterm exam so that analysis could be carried out on the responses of the same set of students exposed to both the modes of teaching imparted by the same teacher. With an exhaustive literature review to trace the emergence of online classes and the impact of the same on the current generation, the study recorded the students’ responses in the form of a survey questionnaire. The quantitative analysis was carried out using Statistical Package for Social Sciences (SPSS) and the variables were tested for the significance of the relationship using the Pearson Chi-Square test. The findings implicitly confirm that the students are comfortable with both real classes and online classes as far as the instructor is efficient to use appropriate pedagogies and digital tools to support learning.